Revision of Atopida White, 1846 (Coleoptera: Scirtoidea: Scirtidae) - Kiałka, Agata; Ruta, Rafał (Zootaxa, 2022)
Atopida is a New Zealand endemic genus distributed in both North and South Islands. Remarkable sexual dimorphism of most species was a source of numerous misinterpretations in studies by Thomas Broun—males and females of the same species were often described as distinct taxa. After examining type material of all species and over 600 additional unidentified specimens from several institutions, the following new synonyms were established: Atopida grahami Broun, 1910 is a junior synonym of A. hirta Broun, 1880; A. pallidula Broun, 1921 is a junior synonym of A. impressa Broun, 1914; A. basalis Broun, 1912 and A. sinuata Broun, 1893 are junior synonyms of A. proba Sharp, 1878; A. lawsoni Sharp, 1878 is a junior synonym of A. suturalis (White, 1846). The following eight species are newly described: Atopida insularis sp. nov., A. lescheni sp. nov., A. paparoa sp. nov., A. paringa sp. nov., A. tuhua sp. nov., A. waipoua sp. nov., A. walkerae sp. nov., and A. westlandensis sp. nov.